Conceptual framework to provide culturally congruent care to epilepsy patients in selected rural communities in South Africa - Muofheni Nemathaga; Maria S. Maputle; Lufuno Makhado; Ntsieni S. Mashau (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Epilepsy is a neurological disorder affecting millions of people in Africa. Among other reported findings, many people living with epilepsy (PLWE) believe that the condition is caused by spiritual factors. Previous studies have revealed that majority of PLWE are not receiving adequate care and treatment because of diverse cultural beliefs associated with epilepsy. Consequently, they consult either faith-based healers or traditional healers. Others, however, acknowledge the medical causes of epilepsy and seek developed medical treatment.